2016
DOI: 10.2134/jeq2015.10.0528
|View full text |Cite
|
Sign up to set email alerts
|

Surface Runoff of Pesticides from a Clay Loam Field in Sweden

Abstract: Pesticides stored at or close to the soil surface after field application can be mobilized and transported off the field when surface runoff occurs. The objective of our study was to quantify the potential pesticide losses in surface runoff from a conventionally managed agricultural field in a Swedish climate. This was achieved by measuring surface runoff volumes and concentrations in runoff of six spring-applied pesticides and autumn-applied glyphosate and its metabolite aminomethylphosphonic acid (AMPA). Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Nevertheless, the available literature suggests that, in some regions, such artificial structures like roads, pipes, or ditches are important for connecting fields with the stream network. For example, this was reported in the regions of Alsace (France; Lefrancq et al, 2013), Lower Saxony (Germany; Bug and Mosimann, 2011), Baden-Württemberg (Germany; Gassmann et al, 2012), and Rhineland-Palatinate (Germany; Rübel, 1999). Based on our findings, we hypothesize that shortcuts are mainly important in areas with small field sizes.…”
Section: Relevance In a Broader Geographical Contextsupporting
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, the available literature suggests that, in some regions, such artificial structures like roads, pipes, or ditches are important for connecting fields with the stream network. For example, this was reported in the regions of Alsace (France; Lefrancq et al, 2013), Lower Saxony (Germany; Bug and Mosimann, 2011), Baden-Württemberg (Germany; Gassmann et al, 2012), and Rhineland-Palatinate (Germany; Rübel, 1999). Based on our findings, we hypothesize that shortcuts are mainly important in areas with small field sizes.…”
Section: Relevance In a Broader Geographical Contextsupporting
confidence: 70%
“…Undrained roads were reported to intercept flow paths, to concentrate and accelerate runoff, and, therefore, also to influence pesticide connectivity within a catchment (Carluer and De Marsily, 2004;Dehotin et al, 2015;Heathwaite et al, 2005;Payraudeau et al, 2009). Additionally, Lefrancq et al (2013) showed that undrained roads act as interceptor of spray drift, possibly leading to significant pesticide transport during subsequent rainfall events when intercepted pesticides are washed off the roads.…”
mentioning
confidence: 99%
“…These results indicate, although rather indirectly, that macropores play a larger role for the transport of substances of more intermediate mobility, as argued by McGrath et al (2010), and that this also applies to frozen soil. More mobile substances may leach regardless of the presence of macropores, whereas more or less immobile substances adsorb strongly to the soil in any case and are transported either particle‐bound through macropores toward drains (Kjær et al, 2011; Øygarden et al, 1997) or via surface runoff/erosion (Larsbo et al, 2016). The fact that diflufenican was found in very low concentrations in leachate in this study may, among other reasons (sorption, degradation), be due to loss via particle‐bound transport.…”
Section: Discussionmentioning
confidence: 99%
“…Pesticides are lost to surface waters through various pathways from either point sources or diffuse sources. In current research, surface runoff (Holvoet, Seuntjens, and Vanrolleghem 2007;Larsbo et al 2016; Lefrancq et al 2017), preferential flow through macropores into the tile drainage system (Accinelli et al 2002;Leu et al 2004a;Reichenberger et al 2007;Sandin et al 2018), and spray drift (Carlsen, Spliid, and Svensmark 2006;Schulz 2001;Vischetti et al 2008) are considered of major importance. Other diffuse pathways like leaching into groundwater and exfiltration into surface waters, atmospheric deposition or aeolian deposition are usually less important.…”
Section: Introductionmentioning
confidence: 99%